Efektivitas Pemberian Terapi Uap dengan Menggunakan Minyak Kayu Putih Terhadap Bersihan Jalan Nafas Tidak Efektif Pada Pasien ISPA di Puskesmas Namo Terasi - Dhea Frisca Br. Sembiring; Mhd. Taufik Daniel Hasibuan (PT. Hasba Edukasi Mandiri, 2025)
Acute Respiratory Infection (ARI) is an acute inflammation of the upper and lower respiratory tract caused by bacteria and viruses without or accompanied by inflammation of the lung parenchyma. One effort to overcome ineffective airway clearance is warm water steam therapy and eucalyptus oil. Inhaling eucalyptus oil can relieve respiratory problems, because eucalyptus oil vapor acts as a decongestant which, when inhaled, can reduce nasal congestion and facilitate breathing. Objective: To see the effectiveness of providing steam therapy using eucalyptus oil for ineffective airway clearance in ISPA patients at the Namo Terasi Community Health Center. Method: The research method used is Quantitative Pre-Experimental design and uses One Group Pretest – Posttest. The sampling technique uses Random Sampling. Results: The results of the research show the effectiveness of giving steam therapy using eucalyptus oil for ineffective airway clearance in ISPA patients at the Namo Terasi Community Health Center with the result of p-value = 0.000 which is said to be influential if the p-value < α (0.005). Conclusion: The effectiveness of steam therapy using eucalyptus oil on airway clearance is not effective in ISPA patients at the Namo Terasi Community Health Center. Suggestion: It is hoped that future researchers can continue this research with the same or different interventions.